Implementation of tahfidz itqon method based on differentiation of early childhood potentials - Imam Mawardi; Aziz Muzaki; Irma Sulistiyaningrum; Nashih Muhammad; M. Rohiq; Zainal Arifin (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to determine the implementation of variations in learning tahfidzul Qur'an with the ITQON method based on differentiation in early childhood at Tahfidzul Qur'an Al Ikhlash Islamic Kindergarten in Krogowanan, Sawangan, Magelang. This research is a descriptive qualitative research with a case study approach. The subjects in this study were caregivers from both the school principal and the ustadz. Data collection techniques were obtained from documentation in the form of guidelines for implementing tahfidz activities, standard operating procedures, and other data such as documents regarding the condition and program of children's activities. Data analysis techniques used include data reduction, presentation of data results, and drawing conclusions. The results of the study show that the use of the ITQON method based on differentiation can strengthen thinking skills, be able to process information well, broaden understanding, and can provide feedback in increasing memorization of the Qur'an according to different levels of early childhood abilities.